Late Quaternary marine records from High Arctic Canada: problems, solutions, and multiproxy perspectives - Pieńkowski, Anna J.; Furze, Mark F.A.; England, John H.; MacLean, Brian; Von Prause, Markus; Blasco, Steve (My University, 2013)
The Canadian Arctic Archipelago (= CAA) constitutes a significant geographic region within the Arctic Ocean Basin, influencing its oceanography, biology, ecology, and climate. Yet comparatively little is known about the long-term (post-Late Wisconsinan) environmental history of the marine channels of this region (the “Northwest Passage” = NWP). New marine data emerging from the central CAA extending back to regional deglaciation highlight the potential of multiproxy approaches in high-latitude settings.
Presented on April 8, 2013 at the European Geosciences Union General Assembly in Vienna, Austria.
Keywords: glaciation; Canadian Arctic Archipelago